Exploring the Factors Influencing the Use of Communication and Collaboration Applications - Maican, Catalin; Cazan, Ana-Maria; Lixandroiu, Radu; Dovleac, Lavinia; Maican, Maria Anca (IGI Global, 2021)
Over the recent years, online communication and collaboration applications have been extensively used in teaching, learning, and research. The aim of the present study is to evaluate the attitudes and perceptions of higher education students concerning these applications and their use in learning activities. The research was conducted on 748 Romanian students. The findings have revealed that social networks represent the main category of communication and collaboration applications used for learning purposes. Additionally, gender-induced differences have been found, as well as variances among undergraduates and graduates by several dimensions of the unified technology acceptance model, while students' learning engagement proved to mediate the relationship between personality traits, technology self-efficacy, and the use of collaboration tools. The paper also offers a comparative analysis between the students' and the academics' responses to the use of online communication and collaboration applications in the same cultural and organizational context. Practical implications are also presented.